An atlas of early human mandibular endochondral and osteogenic paracrine signaling regions of Meckel’s cartilage - Zongshan Shen; Ran Zhang; Xinyue Chen; Guan Yang; Yuanchun Si; Tianxing Yan; Suwen Chen; Bin Cheng; Xiaoshan Wu; Di Chen; Dong Zhang; Guozhi Xiao; et al. (Proceedings of the National Academy of Sciences, 2025)
The mandible, also known as the lower jaw, is the only bone in the skull that can move and is essential for speaking and chewing. Meckel’s cartilage (MC) is a temporary structure that supports the formation of the mandible, but how MC is involved in the ossification of the mandible is poorly understood. Through the use of single-cell RNA sequencing and single-cell spatial transcriptomics analyses, a spatiotemporal atlas of MC in human fetuses from 7 to 15 wk postconception was established, highlighting the role of MC in the ossification of the mandible. Importantly, we revealed that two populations of MC contributed to mandibular ossification through different mechanisms. The anterior MC can differentiate into osteolineage cells, as shown in an in vivo lineage tracing mouse model. The intermediate MC facilitates intramembranous ossification through cell–cell communications, possibly through signaling ligands like BMP5 , BMP7 , SEMA3A , PDGFC , and FGF7 . This study suggests that MC plays a crucial role in mediating mandibular ossification through distinct mechanisms, providing valuable insights for understanding oral and craniofacial diseases and disorders in the future.